Wage Formation and the Relation between Real Wages and Unemployment in Sweden - Åsa Eriksson (Lund University, School of Economics and Management, Department of Economics, 2005)
This paper examines the determinants of the wage level and the relation between the wage level and unemployment in Sweden between 1982 and 2002, using a cointegrated VAR approach. The long-run relation between wages and unemployment is found to be negative. There is also evidence of large deviations between the development in real wages and the development in productivity, in that the growth in real wages exceeds the growth in labour productivity. The results indicate that rigidities are present in the Swedish labour market and that these rigidities may cause higher unemployment. Furthermore, trade unions are found to have a large influence on the wage formation process.
Keywords: C32; E24; 330; Wage formation; Unemployment; Cointegration; Common Trends